Defensive healthcare practice: systematic review of qualitative evidence - James Thomas; Melissa Harden; Theo Lorenc; Claire Khouja; Helen Fulbright (BMJ Open)
Objective To synthesise qualitative evidence on clinicians’ views and experiences of defensive practice.Design Systematic review of qualitative data.Data sources MEDLINE, Embase, PsycINFO, AMED, Maternity and Infant Care, CINAHL, ASSIA, Sociological Abstracts, Proquest Dissertations & Theses and PROSPERO were searched from 2000 to October 2023.Eligibility criteria We included English-language studies of clinicians which reported qualitative data on the impact of litigation or complaints on clinical practice.Data extraction and synthesis We coded findings data line by line using a grounded theory approach. We assessed quality using Hawker et al’s tool and synthesised data thematically.Results 17 studies were included. Participants identify a range of clinical decisions which may be defensively motivated, relating to diagnosis and documentation as well as to treatment. Defensive practice often relates to a diffuse sense of risk rather than the direct threat of litigation and may overlap with other motivations, such as perceived pressure from patients or the desire to avoid harm. Defensive practice is seen to be harmful in many ways, but again, these perceptions may gain force from broader narratives of mistrust and disempowerment, as much as from the risk of litigation.Conclusions The idea of defensive practice, as enacted, is more complex than some theoretical accounts suggest and may often function to express broader concerns about the work of clinical care. The qualitative evidence calls into question the view of defensive practice as a key mediator linking litigation risk to inappropriate treatment and excess costs.